Rancang Bangun Aplikasi Mobile Bank Sampah Menggunakan Framework React Native dan Rest API - Ahmad Wahyu Rafsan Zani; Kartini Kartini; Agung Mustika Rizki (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Waste Bank is an institution that plays an important role in waste management. Kedungmaling village is a village located in Mojokerto district, East Java province, Kedungmaling Waste Bank was established in 2019 and its head is the PKK organization of Kedungmaling village. Some research has been conducted with a case study of a Waste Bank to improve the performance of waste banks that still carry out their business processes conventionally. Most previous research focused on making waste bank applications but still used Kotlin programming language and fire base web service as the database. This research uses the React Native framework to create mobile applications and uses the Rest API as a database. The application design uses the SDLC method with a waterfall model. Application testing using black box gets a percentage of 97% of 89 scenarios and Rest API testing assisted by the postman application gets a percentage of 100% of 94 scenarios. With this application, it can help officers in managing waste and facilitate customers in managing their balances.